Cognitive Strategy in Second Language Learning: Understanding How Learners Transfer from English to Malay - Vijayaletchumy Subramaniam, M. Patmavlasny (International Journal of Advanced Science and Technology, 2019)
Language transfer is a common phenomenon in a second language (L2) learning environment. This cognitive process involves the use of different methods known as “transfer strategies” in the production of a target language structure. It very much depends on the linguistic element being transferred as different element requires different strategy. However, strategies in the production of noun phrases (NPs) has not gained much attention thus far. Hence, this study investigates how L2 learners produce Malay NPs via transfer from English. Framed within a qualitative case study design, 4 university students were chosen as participants. The methods used in this study are document analysis and interview. The findings indicate that students have used all the 3 types of transfer strategies namely Substitution, Literal translation and Alteration of structure. However, they resulted in erroneous NPs. This information reveals that students must be cautious in using transfer as a learning strategy to avoid unwanted results.